Resistome in gram-negative bacteria from soft cheese in Brazil - Silva, Cristiane Rodrigues; Okuno, Newton Takeshi; Macedo, Victor Hugo Lima de Medeiros; Freire, Isabela da Rocha; Miller, Rafael Monção; Marin, Victor Augustus (Revista de Ciências Médicas e Biológicas, 2020)
ABSTRACT Objectives: evaluation of antibiotic resistance in Gram-negative microbiota from ready-to-eat cheese samples. Methodology: this research applied a specific method to evaluate the phenotypic susceptibility to antibiotics in a viable Gram-negative microbiota. The selected food was a cheese that is commonly consumed without thermal processing, the Minas Frescal cheese. The evaluation was followed by a PCR screening in this resistant microbiota, for genes that provide resistance to antibiotics and also to the quaternary ammonium. Results: all cheese samples demonstrated a resistant microbiota. In 13.3% of the cheese samples analyzed, the resistance reached all ten different antibiotics tested and, in 80%, 8 to 10 different antibiotics. In antibiotics considered critics as the carbapenems: ertapenem presented resistant microbiota in 86.7% of the samples. In cephalosporins, the resistance reached 100% in the third generation (ceftazidime) and almost half of the samples (46.7%) in the fourth generation (cefepime). In genotypic research, seven different resistance genes were found in 69.2% of the bacterial pools, including the beta-lactamase-producing genes ctx, tem, shv, tetracycline resistant genes and a high rate of integrons class 1 and 2. Conclusions: the results indicate phenotypically and genotypically that the Minas frescal cheese can present potential resistant microbiota. Therefore, the methodology used is a viable possibility and with a broader answer about the food microbiota role in resistance. This research corroborates the food area as an important sector to be managed to reduce the process of antibiotic resistance.